2003
DOI: 10.3748/wjg.v9.i7.1501
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of HBV intrauterine transmission: A clinical study

Abstract: The risk of HBV intrauterine infection can be effectively reduced by administration of HBIG or Lamivudine in the 3(rd) trimester of HBsAg positive pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 26 publications
1
113
0
3
Order By: Relevance
“…Those findings suggest that the threshold of HBV DNA 10 8 copies/mL is a potent index of HBV intrauterine infection. To those pregnant women whose serum levels of HBV DNA are high and have high infectivity, we propose to apply highly effective and safe anti-viral medicines to compress the replication of HBV and, therefore, rapidly and dramatically decrease HBV DNA level to interrupt intrauterine infection [11] . In this study, the intrauterine infection rate in the HBIG group and control group were 10.5% and 27.3%, respectively, which suggested that the intramuscular administration of HBIG regularly before delivery could effectively interrupt HBV intrauterine infection [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Those findings suggest that the threshold of HBV DNA 10 8 copies/mL is a potent index of HBV intrauterine infection. To those pregnant women whose serum levels of HBV DNA are high and have high infectivity, we propose to apply highly effective and safe anti-viral medicines to compress the replication of HBV and, therefore, rapidly and dramatically decrease HBV DNA level to interrupt intrauterine infection [11] . In this study, the intrauterine infection rate in the HBIG group and control group were 10.5% and 27.3%, respectively, which suggested that the intramuscular administration of HBIG regularly before delivery could effectively interrupt HBV intrauterine infection [12] .…”
Section: Discussionmentioning
confidence: 99%
“…For women who become pregnant while receiving oral NA therapy, current guidelines recommend continuing treatment if the drug is a category B drug such as telbivudine and tenofovir [34]. Emerging evidence suggests that the use of lamivudine in the last month of pregnancy might prevent mother-to-infant transmission of HBV in women with high HBV DNA levels [36][37][38][39][40].…”
Section: Antiviral Treatment Options For Chb In Women Of Childbearingmentioning
confidence: 99%
“…The consequences of HBV infection due to poor screening and low vaccination rate are that of vertical transmission of hepatitis B virus which has become the major route of transmission of the virus in Nigeria. Shi, et al [19] showed that besides the WHO recommended joint immunoprophylaxis starting from the newborn, multiple injections of small doses of hepatitis B immunoglobulin (HBI g, 200-400 1 u per month) or oral Lamivudine (100 mg per day) in HBV carrier mothers with a high degree of infectiousness (>106 copies/ml) in late pregnancy effectively and safely prevent HBV intrauterine transmission, which provide new insight into preventing HBV at the earliest stage [19,20].…”
Section: Introductionmentioning
confidence: 99%